Forensic Science: A Review - Soni, Surbhi; Bhavya; Pareek, Bhawna; Bhatia, Manisha (Contemporary Advances in Science and Technology, 2022)
Forensic Chemistry involves the application of chemistry and covers up it’s numerous subfield and can be defined as practice of relevance of our knowledge in the field of chemistry to solve complicated criminal cases. Forensic science is crucial for the efficient administration of justice and case investigation. There are many methods that we can adopt from chemistry which help in solving criminal cases. During this process, the increased accreditation and interflow highlighted the role of consensus in forensic standards for forensic service providers to avoid uncertainty regarding the methods used and interpretation of results. Forensic chemist is a person who does effort to identify, quantify and evaluate unknown items at crime scene. General methods employed in Forensic science includes chromatography, spectroscopy, electrophoresis etc. By using these methods and their types we can analyse the samples obtained at crime scene or samples picked up from crime scene and can find out the culprit. This chapter discusses the detailed information about forensic science and role of chemistry in this field.